A Common Body of Professional Knowledge for Internal Auditors: A Research Study (Book). - Hendrickson, Harvey S.; Flesher, Dale L. (The Accounting Review, 1986)
Reviews the book "A Common Body of Professional Knowledge for Internal Auditors: A Research Study," by Michael J. Barrett, Gerald W. Lee, S. Paul Roy and Leticia Verastegui.